SCREENING OF MICROFUNGI FROM SOYBEAN (GLYCINE MAX L.) SEEDS - S. K. DWIVEDI; RAM GOPAL (International Journal of Pharma and Bio Sciences, 2014)
Seed health testing by studying the seed-borne fungi of soybean seeds is an important step in the management of the seed-borne diseases. In the present study seed-borne fungi was studied by using agar plate method. A number of seed-borne fungal species was isolated from the agar plate. These seed-borne fungal sps. were Aspergillus niger, A. flavus, A. fumigatus, Chaetomium globosum, Curvularia lunata, C. geniculata, Nigrospora sphaerica, Macrophomina phaseolina, Penicillium sp., P. citrinum, Rhizopus nigricans, Trichoderma sp., Alternaria alternata, Dreschslera australiensis, Fusarium oxysporum, F. moniliforme, F. solani and Rhizoctonia solani. Out of these the frequency of Aspergillus flavus and Fusarium oxysporum was higher.